A calculation method for high-speed railway capacity based on improved train deduction method - Li, Xiaojuan; Huo, Yueying; Yan, Zhenying (Transport, 2023)
A reasonable calculation of railway capacity is very important for research. With the rapid development of high-speed railways, more and more differences between traditional and modern railways have emerged in the transportation organization and capacity calculation methods. In this article, the calculation methods used under different conditions with different train types are studied based on the train deduction method. Train deduction is a method that calculates the number of trains that cannot pass through the line when other trains change their stop plan or operation speed based on the coefficient of deduction method, which is widely used in China. Then, optimized models for trains with the same-speed and different-speeds are built to determine the maximum number of trains. These models are built based on the constraints of passenger service quality and overtaking times. In addition, the models are solved based on a train operation plan. Hence, the capacity calculated by these methods is more reasonable for the actual condition. Finally, an actual case of Beijing–Shanghai high-speed railway is implemented and tested with the model. The optimal capacity scheme is simulated and analysed, and the result agreed well with the railway transport enterprise. First published online 5 February 2024